Status of soil quality in south-west of Romania and its role in sustainable development of the rural space - Tarau, Dorin; Borza, Iacob; Dicu, Daniel (Acta Agraria Debreceniensis, 2010)
Being aware of lands ecological resources’ natural conditions and particularities for different uses and crops is of great importance for the big and small producers. In this paper we present the main aspects regarding the quality of the ecopedological conditions. Here there are briefly presented the physico-geographic conditions and the telluric-edaphic configuration of the area. Also, the structure of the main categories of agricultural activities in the physical geographical areas (mountains, hills and plateaus, high and low plains and meadows) and main soils’ types and associations are presented. Lands vocation for different use (arable, lawns, hay, orchard, vineyard The paper ends with highlighting the necessary measures for a lasting administration of ecopedological resources in the studied area.